Letter from Secretary of Publicity Committee to Lambeth Trades Council, 11 May 1926, re: refusing permission to operate printing press
1926-05-11 "Letter from Secretary of Publicity Committee to Lambeth Trades Council, 11 May 1926, re: refusing permission to operate printing press" [g0979001.jpg], 11 May 1926 TUC Organisation